Adaptive control in interpreters: Assessing the impact of training and experience on working memory. Issue 4 (17th August 2020) - Nour, Soudabeh; Struys, Esli; Stengers, Helene
Abstract: The adaptive control hypothesis predicts adaptation of control mechanisms as a response to intensive language use in bilinguals. The present study aims to investigate this hypothesis in two memory experiments with professional and student interpreters. In experiment 1, we compared a group of interpreting students to translation students using a reading span task to test working memory (WM) and a digit span task to test short-term memory (STM). In experiment 2, we added a group of professional interpreters and compared them with the participants in experiment 1. Training-related improvement was found for WM but not for STM, with no differences between both student groups. Professional interpreters with over 20 years of interpreting experience showed better performance than translation students but not than interpreting students both on WM and STM. The results are discussed in light of the framework of interpreting as a type of extreme bilingualism.